LEGALITAS KIAI SEBAGAI WALI DALAM PERKAWINAN TANPA WALI NASAB - Muhammad Sirojudin Sidiq (As-Salam: Jurnal Studi Hukum Islam & Pendidikan, 2015)
Kiai as a guardian in marriage is a phenomenon that is not uncommon among Islamic societies, especially in rural communities that tend to study Islamic law through the books of fiqih salaf, which until now still cause pro-cons among the kiai / Scholars and other Islamic societies. The issue discussed in this paper is the argument of the legality of kiai as a guardian in marriage without the guardian of Islam according to Islamic law and the legislation in Indonesia, in order to explain the kiai’s argument as a guardian in marriage, to explain the legal basis arising from the kiai as the guardian in Marriage under Islamic law and legislation. The results of this study indicate that the kiai’s law as a guardian in marriage without guardian nasab, marriage is considered unlawful according to laws and regulations applicable in Indonesia and illegitimate according to jumhur ulama, because the guardians who should carry out are the judges and not the kiai